Voice effects due to the use of mask and musculoskeletal injuries in teachers - Sandoval Zúñiga, María Soledad; Fuenzalida Cabezas, Rodrigo; Sandoval Contreras, Manuel; Opazo Salgado, Mirna; González Muñoz, Yocelyn (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Prolonged use of voice is a risk factor for developing vocal pathologies in teachers. Currently, these professionals are forced to wear a mask to teach, which can result in a vocal alteration. During the virtualization of classes, teachers had to adapt some domestic space to dictate their classes in front of a computer, reducing physical activity and promoting a sedentary lifestyle, which could cause some musculoskeletal disorder. With this panorama, the purpose of this study is to identify effects on voice for using mask and musculoskeletal injuries in teachers.